KEBERLAKUAN ASAS NE BIS IN IDEM TERHADAP PUTUSAN PENGADILAN ADAT DALAM TATA HUKUM INDONESIA - Masril Masril; Ade Kosasih (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstract: The number of cases have been decided and executed by the Customary Court, but are still being processed and tried according to national law. It creates legal uncertainty and tends to conflict with the values of justice and human rights. This tendency is due to law enforcers who prioritize the principle of nullum delictum noella poena sine pravea lege poenali. The criminal law also acknowledges the principle of ne bis in idem for every decided and executed cases, including the Decision of the Adat Court. The result describes that the application of the principle of ne bis in idem to the Decision of the Customary Court has a place in Indonesian law. This can be recognized from the existence of a Supreme Court jurisprudence which states that if a case has been decided by the Adat Court and brought back to court, the Public Prosecutor's indictment must be declared